DEEPENING SOCIAL INEQUALITIES AND SLOWING DOWN ECONOMIC GROWTH DUE TO CORRUPTION, UNDERGROUND ECONOMY AND TAX EVASION - Adrian-Ducu, MATEI; Cristiana, MATEI (Strategii Manageriale, 2014)
The article highlights some sources of inequalities in a globalized world which does not only generate positive impact. In the event it is mismanaged, globalization can give life to a mechanism facilitating tax evasion and, in the same time, ensuring for a small group of individuals, a power position not only when negotiating inside a company but also across the political life of a society. Moreover, the most important traits of corruption and underground economy are marked out in relation to the deepening of social inequality in Romania. These negative phenomena are also present due to the malfunctioning of the market, strengthened monopolies, hindered competition and excessive use of asymmetric information. In the current context of an economic and financial crisis, one much linked to trust, phenomena such as corruption, underground economy and tax evasion have become omnipresent, hot topics in both Romania and Europe. This is how the economy is taken over and significant resources of the public budget are missed by the state. The consequences are severe and can lead to incapacity to ensure a decent standard of living and ultimately social peace. A continuous attempt to curb these phenomena could and should be a priority and a method to settle the public financial equilibrium in Europe and in Romania in particular.